How Preschool Teachers Handle Problem Situations: Discussing Some Indicators of Emotional Issues - Derya Şahin Ası; Damla Güzeldere Aydın; Şakire Ocak Karabay (European Teacher Education Network, 2018)
Teachers usually interact with their students in various ways including instruction. If there is a conflict occurs between child and teacher, teachers may have the tendency to use several strategies to regulate this position. Teachers who may not know or not have adequate skills how to handle problems or problem behaviors of children within classroom may lead children to experience various forms of emotional maltreatment. In this study, we focused on emotional maltreatment reported by teachers when they encounter problem behaviors of their students or conflicts within the classroom. It was a qualitative study with 91 female preschool teachers from ten schools. We prepared four semi structured questions to ask about typical problem situations they might encounter within their classes. Teachers were supposed to answer questions based on their experiences and/or opinions concerning how they would handle those kinds of situations. They mostly repeated deprivation which means removing materials/resources that make child feeling comfortable, threatening to remove materials/resources from the physical environment, not being sensitive enough to the needs of child, embarrassing child in front of others, ignoring child who has problem by leaving on his/her own. Results were discussed based on teachers' role within interactions in a classroom context to affect their emotions, thinking styles, well-being and involvement in classroom activities.